Comparison of morrow procedure and transapical beating-heart septal myectomy in patients with hypertrophic obstructive cardiomyopathy: a systematic review and meta-analysis - Zhakayev, Maxat; Tuleutayev, Rustem; Nurbay, Zhanar; Izmailovich, Marina (Frontiers in Surgery, 2025)
IntroductionTransaortic surgical myectomy is the established gold-standard treatment for hypertrophic obstructive cardiomyopathy (HOCM). In contrast, the less invasive transapical beating-heart septal myectomy (TABSM) has recently gained attention as a potential alternative, although comparative evidence regarding their clinical outcomes remains limited.ObjectivesTo compare the efficacy and safety of surgical myectomy and TABSM in patients with HOCM.MethodsA systematic search of PubMed, Web of Science, Cochrane Library, and ScienceDirect (January 2014–May 2025) identified 24 observational studies including 3,732 patients (2,824 surgical myectomy; 908 TABSM). The primary outcome was the change in left ventricular outflow tract pressure gradient (LVOTPG). Secondary outcomes included improvement in NYHA class, prevalence of moderate-to-severe mitral regurgitation (MR ≥ 2), short-term (30-day) and long-term mortality, and the rate of postoperative permanent pacemaker implantation. Random-effects meta-analysis and meta-regression were performed.ResultsBoth procedures achieved substantial and comparable reductions in LVOTG, with no significant between-group difference (p = 0.75). Functional status improved in both cohorts; younger age and higher study quality were independently associated with greater improvement in NYHA class (p < 0.05). Residual MR ≥ grade 2 decreased in both groups. 30-day mortality was low and similar between surgical myectomy and TABSM. Long-term mortality appeared lower after TABSM (≈2%) compared with surgical myectomy (≈6%); however, this finding should be interpreted cautiously due to substantial heterogeneity and shorter follow-up in TABSM studies. Pacemaker implantation occurred less frequently after TABSM than after surgical myectomy (≈2% vs. ≈6%; p = 0.03).ConclusionBoth surgical myectomy and TABSM are effective and safe approaches for septal reduction in HOCM. While surgical myectomy remains the reference standard, TABSM represents a promising minimally invasive option, particularly in anatomically complex or reoperative cases. Prospective studies with standardized endpoints are required to guide individualized procedural selection and confirm long-term outcomes.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251075522, Identifier CRD420251075522.